Extraction and characterization of chitin and chitosan with antimicrobial and antioxidant activities from cosmopolitan Orthoptera species (Insecta) - Kaya, Murat; Baran, Talat; Asan-Ozusaglam, Meltem; Cakmak, Yavuz Selim; Tozak, Kabil Ozcan; Mol, Abbas; Mentes, Ayfer; Sezen, Goksal (Biotechnology and bioprocess engineering, 2015)
This study examined two gregarious Orthoptera species (Calliptamus barbarus and Oedaleus decorus) as potential sources of chitin. The chitin content of the dry weight of C. barbarus was 20.5 ± 0.7%, and it was 16.5 ± 0.7% for O. decorus. Furthermore, the yield of chitosan (70 ~ 75% deacetylation degree) from the grasshopper species was found to be 74 ~ 76%, which is close to the yield of commercial preparations obtained from the unused parts of crabs and shrimp. The chitin and chitosan obtained in this way were analyzed using FTIR, TGA, XRD and SEM techniques, and the antimicrobial properties of chitosans obtained from C. barbarus and O. decorus against pathogenic microorganisms of humans and fish were investigated using the disc diffusion and microdilution broth methods. The antimicrobial screening procedures indicated that the chitosan showed significant antimicrobial activity against all of the tested pathogenic microorganisms. The MBC or MFC values were determined to be 0.16 ~ 2.50 mg/mL. The IC₅₀values for the chitins obtained from C. barbarus and O. decorus were 10.68 ± 0.27 and 10.91 ± 0.96 mg/mL, respectively, which were greater than the value for butylated hydroxytoluene (BHT): 0.04 ± 0.01 mg/mL. These results suggest that these two species, which are currently considered to be pests because of over-breeding, are potentially alternative sources of chitin and chitosan, which are used in the food/feed industry for their antimicrobial and antioxidant properties.